Manganese Removal in Groundwater Treatment Using Marble - Athirah, Ainul Afeeqah (International Journal of Integrated Engineering, 2019)
Manganese is one of difficult elements to remove in groundwater due to its high solubility in both acid and neutral condition. Thus, this study has investigated the groundwater treatment using high purity marble (>97%) in removing manganese. Groundwater sample was taken at USM’s Engineering Campus, Malaysia and the concentration of manganese is approximately 0.5 ppm exceeding the Malaysia Water Quality Standard at 0.1 ppm. Filtration of groundwater using pebble size marble and sand size marble column filter was done with different flowrate. For pebble size marble column filter, the highest percentage removal is 58.15% where the flowrate is 0.007 L/s. On the other hand, for sand size marble column filter, the highest percentage removal is 97.26% where the flowrate is 0.017 L/s. Sand size marble particle shows an efficient manganese removal in groundwater compared to pebble size particle.